Technical barriers to trade (WTO GenevaCH, 2013)
Discusses the text of the TBT Agreement as it appears in the Final Act of the Uruguay Round of Multilateral Trade Negotiations, signed in Marrakesh on 15 April 1994. Presents the basic structure of the WTO Agreements. Provides a brief overview of the background, purpose and scope of the agreement, as well as the type of measures it covers. Sets out key principles and discusses how these have been addressed in recent disputes. Contains the full text of the TBT agreement, decisions and recommendations of the TBT Committee, a list of observers and an example of a typical TBT notification.
Keywords: TRADE BARRIERS